La imagen, el cuerpo y las mercancías en los procesos de translocalización religiosa en la era global = The image, body and merchandise in the processes of religious translocation in the global era - Torre, Renée de la (Ciencias sociales y religión, 2008)
A characteristic in the contemporary world culture is territorial mobility which causes, within and among cultures, that religions modify their ways of being implanted by fading and making flexible their territorial roots and thus, reassessing the corporal unit as the privileged locus of religious experience. A modern phenomenon is translocalization and relocalization of traditional religions. Comprehension of these dynamics demands us to review the conceptual postulates of religious experience, body, ritual and space.